Radiological assessment of shoulder balance following posterior spinal fusion for thoracic adolescent idiopathic scoliosis. Issue 2 (December 2015) - Namikawa, Takashi; Matsumura, Akira; Kato, Minori; Hayashi, Kazunori; Nakamura, Hiroaki
Abstract Background The objective of this study was to evaluate shoulder balance following posterior spinal fusion for thoracic adolescent idiopathic scoliosis (AIS). Methods Twenty-four patients (22 females) with thoracic AIS who had undergone posterior fusion with segmental pedicle screws were retrospectively reviewed. The mean follow-up duration was 29 (range, 24–55) months. Fifteen patients had type 1 curves, seven had type 2 curves, and two had type 3 curves according to the Lenke classification. The proximal thoracic (PT) and main thoracic (MT) Cobb angles, percent correction of PT (PTC) and MT (MTC) curves, T1 tilt, and shoulder asymmetry according to radiographic shoulder height (RSH) were measured on preoperative, immediately postoperative, and final follow-up radiographs. The preoperative PT and MT curve side-bending percent correction (PTBC and MTBC) were also measured. The PTC:MTC ratio was employed as an index of PTC and MTC matching. Patients were divided into two groups according to radiographic findings immediately postoperatively: the balanced group (|RSH| <20 mm) and imbalanced group (|RSH| ≥20 mm). The preoperative indices (RSH, PTBC, MTBC, PTC, and MTC), preoperative and postoperative T1 tilt, and PTC:MTC ratio were compared between the two groups. Results The mean PT and MT were 33.0° and 64.2° preoperatively, 16.1° (50.5%) and 16.8° (74.0%) immediately postoperatively, and 16.9° (49.0%) and 19.2° (70.3%) at final follow-up, respectively. The mean preoperative RSH of −12.3 mm changed to +11.1 mm immediately postoperatively and improved to +5.7 mm at final follow-up. Seventeen patients were "balanced" and seven were "imbalanced" immediately postoperatively. There were significant differences in the PTC (p=0.04), postoperative T1 tilt (p=0.04), and PTC:MTC ratio (p=0.02) between the two groups (Wilcoxon rank-sum test). Only one patient had an imbalanced shoulder at the final follow-up. She had marked shoulder imbalance immediately postoperatively (RSH: +40 mm). Conclusions Sufficient correction of PT curves that is matched with correction of MT curves is necessary to prevent postoperative shoulder imbalance. Almost all patients in our series had satisfactory results in terms of shoulder balance at final follow-up, but one patient with marked shoulder imbalance immediately postoperatively may have residual long-term shoulder imbalance.